Secondary Teacher Candidates’ Perceptions and Experiences Before, During, and After Conducting A Science Show - Johari, Marlizayati; Said, Hardimah; Roslan, Roslinawati (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The science show is a form of informal science learning (ISL) that can potentially develop students' interest in science. However, there needs to be a gap in bridging the ISL elements, such as science shows, into formal teacher education programs as one innovative pedagogical approach. Thus, this study investigates how secondary science teacher candidates' perceptions of science displays shifted after carrying out their science shows and explores their shared experiences as part of their teacher training program. Data were collected from 16 secondary science teacher candidates of cohort 2020 based on their written reflections on their experiences before, during, and after conducting science shows. The study found that some science teacher candidates' perceptions of science shows had shifted, and the others had remained the same. The science teacher candidates' everyday experiences during the science show implementation were their effort to conduct a successful demonstration and develop video-making skills.